2020
DOI: 10.1109/comst.2020.2971781
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on 5G Usage Scenarios and Traffic Models

Abstract: The fifth-generation mobile initiative, 5G, is a tremendous and collective effort to specify, standardize, design, manufacture, and deploy the next cellular network generation. 5G networks will support demanding services such as enhanced Mobile Broadband, Ultra-Reliable and Low Latency Communications and massive Machine-Type Communications, which will require data rates of tens of Gbps, latencies of few milliseconds and connection densities of millions of devices per square kilometer. This survey presents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
201
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 538 publications
(258 citation statements)
references
References 69 publications
0
201
0
5
Order By: Relevance
“…These are all anchored on highspeed, low-latency, and high-bandwidth communication, such as provided by 5G. The International Telecommunication Union (ITU) provides requirements to allow for the massive increase in connected devices expected in the coming years, which may reach up to a million machine-type connections per square kilometer (Navarro-Ortiz et al, 2020). In the current pandemic, 5G can help to provide connectivity for collaborative robots and autonomous material movement to ensure workers keep a safe distance from their peers in factories and warehouses, as already used in China, Canada and some European countries (Chamola et al, 2020).…”
Section: Mmtcmentioning
confidence: 99%
See 1 more Smart Citation
“…These are all anchored on highspeed, low-latency, and high-bandwidth communication, such as provided by 5G. The International Telecommunication Union (ITU) provides requirements to allow for the massive increase in connected devices expected in the coming years, which may reach up to a million machine-type connections per square kilometer (Navarro-Ortiz et al, 2020). In the current pandemic, 5G can help to provide connectivity for collaborative robots and autonomous material movement to ensure workers keep a safe distance from their peers in factories and warehouses, as already used in China, Canada and some European countries (Chamola et al, 2020).…”
Section: Mmtcmentioning
confidence: 99%
“…The 5G mMTC umbrella covers both critical applications required for industrial automation, autonomous vehicles and intelligent transport systems, energy, etc. (Navarro-Ortiz et al, 2020), as well as non-critical connections requiring low data rates and low power consumption.…”
Section: Mmtcmentioning
confidence: 99%
“…In VPON scenario based on LR WDM/TDM PON, when the load is low, bandwidth resources can be saved by reducing the number of used wavelengths. According to (1), it can be concluded that the more wavelengths enabled under the same load, the more threads required to fully use idle time slots caused by RTT. The increase in the number of threads will intensify the wavelength-tuning times of ONU and increase the scheduling pressure of the algorithm.…”
Section: A Adaptive Thread Number and Wavelength Number Selection Mementioning
confidence: 99%
“…With the emergence of 5G, the number of users and the demand of network are gradually increasing, and the distribution scope of users is gradually expanding [1]. In order to enlarge the coverage of access network and increase the number of users that can be loaded, long-reach access network technologies have appeared one after another, such as: long reach passive optical network (LR-PON) [2][3][4][5][6], long reach wavelength division multiplexing / time division multiplexing passive optical network (LR WDM/TDM PON) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Similarly, experts estimate that more than 50 billion devices will be connected to the internet by 2020, and majority will be mobile devices coupled with Internet of things (IOT) devices, which consume high amount of energy compared to a personal computer. 3,4 Therefore, a novel wireless communication system, which can achieve high data rate, high spectral efficiency, wide coverage, and low-latency coupled with energy efficient, is required. 5 One of the major setbacks in wireless communication affecting the quality of service is the fading effect.…”
Section: Introductionmentioning
confidence: 99%